Patients with idiopathic recurrent miscarriage show higher levels of DR+ activated T-cells that are less responsive to mitogens. (November 2015) - Kuon, R.J.; Schaumann, J.; Goeggl, T.; Strowitzki, T.; Sadeghi, M.; Opelz, G.; Daniel, V.; Toth, B.
Highlights: Patients with idiopathic recurrent miscarriage (iRM) have a higher level of DR+ T-cells. T-cells of iRM patients show decreased in vitro proliferation. These disorders resemble T-cell exhaustion in patients with HIV and cancer. Abstract: In 50% of recurrent miscarriages (RM) the cause remains unknown and standardized immunological diagnosis and treatment of idiopathic RM (iRM) is yet not established. In this prospective case-control study, out of 220 RM patients screened, 97 iRM patients were identified and compared to 26 healthy controls without a previous pregnancy or blood transfusion in order to identify deregulated immunological parameters. Blood levels of lymphocyte subpopulations, cytokines and neopterin were determined by FACS, ELISA, and Luminex technique. Lymphocyte function was studied by in-vitro lympocyte proliferation tests. As compared to controls, patients had significantly higher proportions of activated CD3+DR+, CD4+DR+ and CD8+DR+ lymphocytes, elevated levels of neopterin and a lower in-vitro proliferation of lymphocytes (all p  < 0.05). Within the iRM patients higher proportions of CD3+DR+ T-lymphocytes correlated with higher proportions and absolute numbers of CD4+DR+ and CD8+DR+ T-lymphocytes and lower CD16+CD56+ NK-cells. Further, it was associated with lower absolute numbers of CD19+ B-lymphocytes, CD3+CD25+ T-lymphocytes and CD45+ total lymphocytes (all p  < 0.05). In addition we found decreased in-vitro lymphocyte proliferation in iRM patients with high CD3+DR+ T-lymphocytes ( p  < 0.05). In summary patients with iRM showed increased activated T-cells that are less responsive to mitogens in-vitro. The inverse relationship of increased DR but decreased CD25 expression on CD3+ T-cells and the decreased in-vitro proliferation characterize an immunological disorder with similarities to T-cell exhaustion in patients with HIV and cancer. These abnormalities potentially contribute to the pathogenesis of iRM and might be a target for future immunomodulatory therapies.